Cryo-EM fibril structures from systemic AA amyloidosis reveal the species complementarity of pathological amyloids - Falk Liberta (Nature Portfolio, 2019)
Systemic AA amyloidosis is caused by misfolding of the acute phase protein serum amyloid A1. Here the authors present the cryo-EM structures of murine and human AA amyloid fibrils that were isolated from tissue samples and describe how the fibrils differ in their fundamental structural properties.